2020
DOI: 10.1002/pon.5542
|View full text |Cite
|
Sign up to set email alerts
|

The role of Connected Health technologies in supporting families affected by paediatric cancer: A systematic review

Abstract: Objectives Families impacted by paediatric cancer are met with logistical, financial and psychological impacts, with severe acute respiratory syndrome coronavirus two creating additional barriers and stressors for these families. Connected Health (CH) may facilitate cancer care. The objective of the present study was to systematically review CH for families/informal caregivers affected by paediatric cancer. Methods Using search terms relating to: (1) paediatric cancer, (2) family/caregivers and (3) CH, the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
(174 reference statements)
0
15
0
Order By: Relevance
“…The remaining 134 reviews met eligibility criteria and were included in the synthesis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 134 reviews met eligibility criteria and were included in the synthesis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 …”
Section: Resultsmentioning
confidence: 99%
“…Many reviews indicated that a meta-analysis was not done due to heterogeneity of methods and outcomes. 13 , 15 , 18 , 21 , 23 , 29 , 40 , 45 , 46 , 49 , 60 , 65 , 69 , 74 , 75 , 86 , 88 , 89 , 90 , 97 , 100 , 104 , 110 , 116 , 118 , 131 , 134 …”
Section: Resultsmentioning
confidence: 99%
“…Present findings highlight the need for HCP inclusion in online information sharing. Connected Health technologies, or two‐way communicative technologies in health, may be an effective means to provide this HCP contact in a manner that is not cost or time intensive (Delemere & Maguire, 2020). Future online information sources for caregivers of children should consider the inclusion of HCPs where possible.…”
Section: Discussionmentioning
confidence: 99%
“…While the present analysis highlights parent and HCP willingness to engage with CH, further exploration of the role CH may pose is needed. While the efficacy and acceptability of CH interventions for paediatric cancer has been found [34], high attrition and poor adherence have been noted [35]. Further, variability in preferences towards digital service delivery has been noted [36], [37].…”
Section: Discussionmentioning
confidence: 99%